Exploration of the integration of microbiology and immunology emerging topics into undergraduate medical education - Margaret E. Bauer; Samina Akbar; Timothy J. Bauler; Jessica Chacon; Erin E. McClelland; Shawn Staudaher; Yuan Zhao (Medical Education Online)
Purpose Medical school educators face challenges determining which new and emerging topics to incorporate into medical school curricula, and how to do so. A study was conducted to gain a better understanding of the integration of emerging topics related to microbiology and immunology in the undergraduate medical curriculum (UME).Methods An anonymous survey with 17 questions was emailed to medical school faculty who teach immunology and/or microbiology through the DR-Ed listserv, the American Society for Microbiology (ASM) Connect listserv, and attendees of the Association of Medical School Microbiology and Immunology Chairs (AMSMIC) Educational Strategies Workshop. Participants were asked about experiences, perceptions, and the decision-making process regarding integrating emerging topics into UME.Results The top emerging topics that were added to the curriculum or considered for addition in the last 10 years included COVID-19, Zika virus, mRNA vaccines, and Mpox (formerly known as monkeypox). Most respondents reported lectures and active learning as the major methods for topic delivery, with most faculty indicating that formative assessment was the best way to assess emerging topics. Content experts and course directors were the most cited individuals making these decisions. Top reasons for incorporating emerging topics into curricula included preparing students for clinical treatment of cases, followed by demonstrating the importance of basic science, and opportunities to integrate basic science into other disciplines. Challenges for incorporating these topics included making room in an already crowded curriculum, followed by content overload for students.Conclusions This study describes the rationale for integrating emerging topics related to microbiology and immunology into UME, and identifies the current new and emerging topics, as well as the main methods of integration and assessment. These results may be used by medical educators to inform curricular decisions at their institutions. Future studies will include developing innovative learning modules that overcome barriers to integration.